2013
DOI: 10.1371/journal.pone.0080293
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide and Paternal Diversity Reveal a Recent Origin of Human Populations in North Africa

Abstract: The geostrategic location of North Africa as a crossroad between three continents and as a stepping-stone outside Africa has evoked anthropological and genetic interest in this region. Numerous studies have described the genetic landscape of the human population in North Africa employing paternal, maternal, and biparental molecular markers. However, information from these markers which have different inheritance patterns has been mostly assessed independently, resulting in an incomplete description of the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 58 publications
6
30
0
1
Order By: Relevance
“…Population studies aimed at characterizing molecular DNA markers in North African populations have shown an uneven genetic landscape [73][74][75][76]. This picture agrees with the spatial patterns of the GM polymorphism.…”
Section: Discussionsupporting
confidence: 75%
“…Population studies aimed at characterizing molecular DNA markers in North African populations have shown an uneven genetic landscape [73][74][75][76]. This picture agrees with the spatial patterns of the GM polymorphism.…”
Section: Discussionsupporting
confidence: 75%
“…We determined descent clusters, ie, groups of men likely to have a common ancestor that was more recent than the age when surnames were established following with a modified version of the heuristic in Martínez-González et al 19 (for further details on determining descent clusters and their ages, see Supplementary Text S1). Several external references were used for comparison as necessary: Catalans and Italians (only for STRs), 19 Gascons, 20 Bavarians, 21 Moroccans, 22 Swedes (www.yhrd.org), and Sephardic Jews. 23 Local haplogroup frequencies were estimated from our data by using descent clusters as sampling units, thus avoiding related individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies observed a higher near eastern component in the Egyptians compared to the other northern African groups [43,44], which was probably due to the prolonged contacts and the geographical proximity between Egypt and the Near East. With the exclusion of the separation along an east-to-west axis, the plot did not highlight any ethno-geographic sub-structure within the two northern African macro-regions.…”
Section: Accepted Manuscriptmentioning
confidence: 94%